FATIN RUSHDI ZORLU AND HIS POSITION ON THE 1954 ALGERIAN REVOLUTION AND THE TRIPARTITE AGGRESSION AGAINST EGYPT 1956 - Prof. Dr. Ameen Abbas Natheir; Hamed Jameel Atiya (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The research deals with the title (Fatin Rushdi Zorlu and his position on the Algerian revolution in 1954 and the tripartite aggression against Egypt 1956) The relationship between Turkey and France, which was occupying Algeria at that time, as well as the Turkish relationship with Egypt, and the position of Fatin Rushdi Zorlu, who was Deputy Prime Minister of Turkey and was particularly concerned with foreign matters, and how he and Adnan Menderes, the Turkish Prime Minister, managed to secretly support the Algerian resistance by providing them with shipments weapons.